The Influence of Entrepreneurship Education, Social Media, E-commerce, and Accounting Information Systems on Entrepreneurial Decision Making in Accounting Students at Dian Nusantara University - Destyana, Destyana; Mareta, Sigit (Journal of Accounting and Finance Management, 2025)
This research aims to determine the influence of entrepreneurship education, social media, e-commerce, and accounting information systems on entrepreneurial decision making in accounting students at Dian Nusantara University. This research uses a quantitative methods. The research sample was taken using purposive sampling method and Slovin formula which amounted to 174 samples from Undira accounting study programme students. This research data uses primary data obtained from distributing questionnaires. This study uses multiple linear analysis and hypothesis testing using the SPSS for Windows version 29 test tool. The results of this research show evidence that entrepreneurship education, social media, and accounting information systems have a positive and significant effect on entrepreneurial decision making, while e-commerce has no effect on entrepreneurial decision making.